Fluency in spontaneous speech predicts individual variance in executive function among seniors. (31st December 2021) - Spencer, Kiah A; Meltzer, Jed A; Robin, Jessica; Xu, Mengdan; Rose, Mira Kates; Bialystok, Ellen
Abstract: Background: Several recent studies have used automated linguistic analysis of naturalistic speech in a picture‐description task (e.g. Cookie Theft) combined with machine learning approaches to distinguish the speech of those with dementia from healthy age‐matched controls. Extension of these techniques to predict continuous variables related to cognitive status offers a means to track the severity of dementia over time and evaluate the effectiveness of interventions. Here we examine the relationship of speech variability to executive function, the ability to manage conflicting information in speeded task performance. Higher executive function confers protection against the clinical manifestation of dementia despite underlying neurodegeneration. Method: In a new sample of 76 healthy adults aged 65‐75, we measured executive function using an extensive test battery, and elicited spoken picture descriptions in the same individuals. The battery included N‐back, Simon task, verbal fluency, Color Word Interference (CWI or Stroop test), Trails A & B, the elevator subtests of the Test of Everyday Attention, and Logical Memory. Two picture description narratives were recorded and subjected to automated analysis generating over 400 linguistic features, grouped into 8 composite measures. Result: Exploratory factor analysis revealed one factor accounting for most variance in the executive function battery. This factor exhibited significant correlations with four of the eight speech composite measures, from strongest to weakest: word finding difficulty, local coherence, lexical richness, and syntactic complexity, reflecting greater fluency in spontaneous descriptive speech. No significant correlations were found with repetitiveness, global coherence, information units, and sentiment. Ongoing analyses include factor characterization of the language measures with a larger normative sample. Conclusion: Older individuals with higher executive function, as captured by common laboratory tests, also exhibit more fluent speech as quantified by automated linguistic analysis. Word finding difficulties may reflect overall slowing of cognitive processes and access to long‐term memory. Automated speech analysis may ultimately serve as an inexpensive and repeatable measure to track cognitive status over time in older adults at risk of dementia.